Workbook for critical thinking - Epstein, Richard L (Wadsworth Pub. Co., 1999)
Contains exercises integrated with the main text, with ample space to answer the exercises in a standardized format. Provides reinforcement of the techniques for analyzing arguments. Contains cartoons from the main text as well as 400 additional cartoons.